Influence of physical activity and mobile phone addiction tendency on depression among Chinese undergraduates - Dong, Baolin; Li, He; Liu, Ruqiang (Frontiers in Psychology, 2025)
ObjectiveThis study explored the influence of physical activity (PA) and mobile phone addiction tendency (MPAT) on depression among Chinese undergraduate students, testing the mediating effect of MPAT and the moderating effect of gender.MethodsThe International Physical Activity Questionnaire–Short Form (IPAQ-SF), the Mobile Phone Addiction Tendency Scale (MPATS), and the Center for Epidemiologic Studies Depression Scale (CESD-S) were administered to 2,121 Chinese undergraduates (46.25% male, aged 19.74 ± 1.822 years) from 10 public and private colleges and universities. Analyses on the mediating effects of mobile phone addiction tendency and the moderating effects of gender were conducted using the PROCESS macro (Version 3.5).ResultsThere was a significant gender difference in undergraduates' PA (r = 0.193, Cohen's d = 0.394, P < 0.001), while the gender differences in MPAT and depression were not significant (P > 0.05). The influence of PA (β = −0.189) and MPAT (β = 0.435) on depression was significant (P < 0.001). The mediating effect of MPAT on PA affecting depression was significant, with a mediating effect size of 15.0%. Moreover, gender moderated the influence of PA on depression, and it also moderated the influence of MPAT on depression.ConclusionThe conclusions corroborate and clarify that MPAT partially mediated the association between PA and depression, and the mediation effects were moderated via gender. This indicates that increasing undergraduates' PA level could effectively avoid MPAT and thus alleviate their depression. Although caution needs to be taken when inferring causal relationships in a cross-sectional design, the present study advances understanding of how undergraduates' PA was related to depression. It also illustrates that educators and parents should pay more attention to undergraduates' PA.